2006
DOI: 10.1093/annonc/mdj117
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant radio-chemotherapy based on platin compounds in patients with locally advanced non-small cell lung cancer (NSCLC): A meta-analysis of individual data from 1764 patients

Abstract: Concomitant platin-based radio-chemotherapy may improve survival of patients with locally advanced NSCLC. However, the available data are insufficient to accurately define the size of such a potential treatment benefit and the optimal schedule of chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
125
1
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 267 publications
(133 citation statements)
references
References 37 publications
3
125
1
4
Order By: Relevance
“…In lung cancer treatment, radiotherapy is often combined with concomitant application of platinum-based chemotherapeutics (24). Platinum-associated toxicities, however, can be severe and often the treatment protocol has to be adapted to deal with this.…”
Section: Discussionmentioning
confidence: 99%
“…In lung cancer treatment, radiotherapy is often combined with concomitant application of platinum-based chemotherapeutics (24). Platinum-associated toxicities, however, can be severe and often the treatment protocol has to be adapted to deal with this.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with locally advanced NSCLC still have poor prognosis. Concurrent platin-containing CRT prolongs survival (Aupérin et al, 2006), despite the increased risk of SPC in longterm survivors. In this study, it is difficult to speculate on the association of SPC with RT because only one SPC was present in the RT field.…”
Section: Discussionmentioning
confidence: 99%
“…Those studies reported that healthy older adults with locally advanced NSCLC benefitted from concurrent chemoradiotherapy similar to younger patients, but experienced higher rates of hospitalization and toxicity. A previous meta-analysis reported that the benefit of concomitant chemotherapy appeared to be greater in elderly compared to that in younger patients (23).…”
Section: Discussionmentioning
confidence: 96%